SOFTWARE FOR SOLVING THE ONE-STEP STOCHASTIC PROBLEM OF PRODUCTION CONTROL (Web of Teachers: Inderscience Research, 2025)
In an article considered software development for algorithm of the decision by one step stochastic problem(task) of production management on language C#.